VOLCANIC RECORDS AND DATING OF THE UPPER HALF OF THE H15 ICE CORE FROM MIZUHO PLATEAU, EAST ANTARCTICA - コウノ, ミカ; フクオカ, タカアキ; フジイ, ヨシユキ; クサカベ, ミノル; KOHNO, Mika; FUKUOKA, Takaaki; FUJII, Yoshiyuki; KUSAKABE, Minoru (National Institute of Polar Research, 1996)
P(論文) Two closely-spaced peaks of electrical conductivity were found at depths between 45 and 50m of the 120-m long ice core drilled at site H 15 in Antarctica by the 32nd Japanese Antarctic Research Expedition in 1991. Chemical analysis of the core containing these peaks revealed that the ice layers were characterized by high acidity and high sulfate concentration suggesting volcanic signals. In order to identify these characteristics, the core was dated using two methods : (1) counting the number of high electrical conductivity peaks resulting from seasonal variations of SO_4^<2-> and NO_3^-, and (2) an empirical model of firn densification. The dating results suggest that the high conductivity is related to deposition of acidic aerosols from the volcanic eruptions of Tambora in 1815 A. D. and of an unknown volcano in 1809 A. D. departmental bulletin paper